Cooperatives: The market spread - Laureys, François; Marcilly, Bénédicte P.; Zongo, Ousseni (Technical Centre for Agricultural and Rural Cooperation, 2010)
A cooperative of shea butter producers in southern Mali uses ICTs to market their product, improve management systems, and train members in new processing techniques.